PERADABAN ISLAM NABI MUHAMMAD SAW PANGLIMA PERANG SEJARAH SOSIAL PERADABAN ISLAM - Nur Wulandari Sunawir, Afrizal, Syawaluddin (STKIP Subang, 2025)
This study aims to determine the Islamic Civilization of the Prophet Muhammad SAW War Commander of the History of Islamic Civilization. This study uses a library research method using a qualitative research approach. The results of the study indicate that the Islamic civilization built by the Prophet Muhammad SAW not only succeeded in uniting the Arabian Peninsula, but also made a major contribution to the political, social, and military developments in the Islamic world. His teachings full of wisdom and justice continue to influence Muslims to this day, making Islamic civilization one of the great civilizations in the history of mankind.